Synthesis of 2-[ 123I and 124I]-iodoisonicotinic acid hydrazide—potential radiotracers for tuberculosis - Somawardhana, C.W.; Sajjad, M.; Amartey, J.K.; Lambrecht, R.M. (International journal of radiation applications and instrumentation. Part A, Applied radiation and isotopes, 1991)
The radiochemical syntheses of methyl 2-[ 123I]-iodoisonicotinate, 2-[ 123I]-iodoisonicotinic acid hydrazide and 2-[ 124I]-iodoisonicotinic acid hydrazide was accomplished. Iodine-123 was incorporated in the methyl ester molecule by an exchange reaction in glacial acetic acid. The average efficiency of iodine exchange reaction was (92.6 ± 4.5)%. This radiotracer was extracted with ether and the solvent was evaporated. The residue was re-dissolved in anhydrous ethanol and treated with hydrazine under anhydrous conditions to obtain 2-[ 123I]-iodoisonicotinic acid hydrazide. The overall radiochemical yield was 69%. Biodistribution data of both radio-tracers in male Sprague-Dawley rats were collected. This is the first report of SPECT radiopharmaceuticals which may be useful for differential diagnosis of intracranial masses (tuberculoma vs glioma), and CNS tuberculosis in immunosuppressed subjects.